The impact of anodization modification on titanium interaction with human osteoblasts and fibroblasts (in vitro study) - Kamonmard Moungthong; Daneeya Na Nan; Pravej Serichetaphongse; Wareeratn Chengprapakorn (PLoS ONE, 2025)
Title The impact of new anodization modification on titanium interaction with human osteoblasts and fibroblasts (in vitro) Purpose To compare the behavior of osteoblast and fibroblast cells, as well as the surface characteristics, of modified anodized titanium surfaces at different voltages with sandblasted and acid-etched titanium surfaces. Methods Twenty titanium discs were fabricated and subjected to 4 types of surface treatments: machined surface, sandblasted and acid-etched surface (SLA), modified anodized A surface at 30V DC and modified anodized B surface at 70V DC. Surface roughness and contact angle were measured. Osteoblast cells were seeded onto titanium discs and evaluated for cell proliferation, Alkaline phosphatase (ALP) activity, Alizarin red staining, and cell morphology with SEM imaging. Immunofluorescent staining was performed to assessed cell adhesion of both osteoblast and fibroblast cells. Statistic analysis was conducted using ANOVA with Tukey post hoc multiple comparisons. Results The topography and osteoblast cell spreading on both modified anodized titanium surfaces differed significantly from machined and SLA surfaces ( p < 0.05). However, there was no significant difference in osteoblast cell spreading between modified anodized surfaces A and B. In addition, anodized surfaces A and B showed significantly higher ALP activity and Alizarin red staining than both SLA and machined surfaces ( p < 0.05 ). For human gingival fibroblast cells, the modified anodized surfaces exhibited significantly higher cell adherence ( p < 0.05 ), followed by the machined surface, with SLA surfaces showing the least adherence. Conclusions The modified anodized surfaces showed superior biocompatibility, enhancing attachment of both osteoblast and fibroblast cells, whereas the SLA surfaces exhibited the least fibroblast cell adherence.